MIDAS: A Middleware to Provide Interoperability between SaaS and DaaS - Marinho, Tarcio; Cidreira, Vinicius; Claro, Daniela Barreiro; Mane, Babacar (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2016: Anais do XII Simpósio Brasileiro de Sistemas de Informação, 2016)
Software as a Service (SaaS) and Data as a Service (DaaS) proves to be two promising areas of research in the cloud computing field, however interoperability among different cloud providers is yet poorly explored. Today, clients looking for content or services from different providers need extra time and resources to learn and implement the required adaptations from the other parties. In this paper we propose MIDAS, a novel middleware to interoperate SaaS and DaaS services seamlessly and independently from provider. That is, SaaS applications will be able to get data from DaaS datasets by sending a query to our middleware and letting it mediate the communication and return the expected results. We evaluate our proposal by developing a prototype from two case studies and by analyzing the time effort to query through our middleware. Our results presented that no important overhead were required from providers nor to the final user.